Evaluasi Kepatuhan Etika Profesi Terhadap Batasan Waktu Kerja Dalam Konteks Kolaborasi Tim Jarak Jauh Global Dan Implikasinya Terhadap Kesejahteraan Ekonomi Karyawan - Dito Aditia Darma Nst; Dewi Apriliya Ritonga; Muhammad Tegar Dwinata; Annisa Gunawan; Andini Putri Lestari; Kristin Paulina; Sonia Arapenta br Purba (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to evaluate professional ethics compliance with working time limits in the context of global remote team collaboration and its implications for employee well-being. The shifting work paradigm due to digital transformation has given rise to the phenomenon of cross-time zone working, encouraging shifts in working hours beyond normal limits, potentially violating professional ethics principles such as autonomy, non-maleficence, beneficence, and justice. Using a qualitative approach through case studies and document analysis, this study found systematic violations of working time limits, resulting in increased burnout, decreased well-being, and an inequitable distribution of the workload. Furthermore, weak implementation of organizational policies, a culture of overwork, and the absence of monitoring mechanisms exacerbate these ethical violations. The study's findings emphasize the need for strengthened regulations, the design of more specific remote work policies, and the implementation of the principle of time zone equity to protect employee well-being in a global collaborative environment.